Validação dos Dados do Saldas para a Região Central do Rio Grande do Sul - Timm, Andréa U.; Moreira, Virnei S.; Roberti, Débora R.; Webler, Geovane; Silveira, Marcos C.; Teichrieb, Cláudio A.; de Gonçalves, Luis G. G.; Degrazia, Gervásio A. (Ciência e Natura, 2011)
.